Vigor germinativo de las semillas botánicas del Piñón Blanco (Jatropha Curcas l.), en Tarapoto – San Martín - Oblitas Rodríguez, Juan Carlos (2010)
In the present investigation, we evaluated the germination of 100 seeds per treatment Piñón, from the ecotype Totorillaico. The collected seeds were stored at room temperature indoors and in refrigeration, storage intervals corresponding to the need to separate at least 15 days between the treatment facility in relation to another, with assessments of an average of 10 days as indicated by Cuculiza (1956), and the availability of seeds needed for research work. In the results, the germination rate of seeds decreases white Sprocket - 3.8532%. Seeds stored at room temperature slightly exceeded those seeds that were stored in refrigeration at 8 ° C without implying differences between them. Germination energy of seeds is a reduction, for every day of storage, the germination rate decreases - 2.615. The seeds were soaked in general not uniformly higher averages obtained germination energy than those seeds that were soaked for 24 hours and dried under shade. Regarding the germination rate index, the overall variation was very small. The seeds without soaking yielded average rate of germination rate with a polynomial behavior and those seeds with 24 hours soaking and 24 hours of drying under shade more linear behavior with respect to storage time.